Meat, milk and more: Policy innovations to shepherd inclusive and sustainable livestock systems in Africa - Malabo Montpellier Panel; Glatzel, Katrin; Tankari, Mahamadou Roufahi; Shah, Meera; Choudhury, Samira; Badiane, Ousmane; von Braun, Joachim (International Food Policy Research Institute, 2020)
Meat, Milk & More: Policy Innovations to Shepherd Inclusive and Sustainable Livestock Systems in Africa highlights options for sustainably promoting growth in the livestock sector, drawing from what four African countries—Ethiopia, Mali, South Africa, and Uganda—have done successfully in terms of institutional and policy innovation as well as programmatic interventions. By adapting these lessons to countries’ specific contexts and scaling them up across the continent, African governments can meet their national and international commitments to agricultural growth and transformation.